The Implementation of SSCS Model By Using MATLAB on Integral Materials (A Case Study for Problem Solving and Creative Thinking) - Assidiqi, Hasby; Sabirin, Muhammad; Paris, Muhammad Amin; Nugroho, Arif Ganda; Atsna, Muh. Fajaruddin (International Journal of Psychosocial Rehabilitation, 2020)
This research is intended to find out math problem solving and creative thinking ability of the students on integral materials by implementing SSCS Model with conventional learning model helped by math laboratory. The method used in this research is true experimental design with posttest only control experimental design. The samples of this research are the students of XII grade of Natural Sciencs of MAN 1, MAN 2, and MAN 3 Banjarmasin with the total number are 216 students. These samples are devided into experiment and control classes. The data in this research are analyzed by using Corhan Formula, Mean Formula, deviation standard, Z- Test, F-Test, T-Test, and Mann Whitney-Test. This research concluded that the math problem solving and creative thinking ability of the students on integral materials in experiment class are in good and very good category, while in control class the two abilities are in good category. Additionally, there is a significant different between the ability of math problem solving and creative thinking implemented by using SSCS Model with conventional learning model helped by math laboratory on the integral materials.